Factor Affecting the Capital Adequacy Ratio of Banks Listed in Indonesia Stock Exchange - Susy Muchtar, Abdurrahman Setiawan, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
The purpose of this study is to conclude the factors that affect bank capital adequacy ratios. The sample used is 42 banks listed on the Indonesia Stock Exchange in 2015-2019. The analysis method used was panel data regression and using purposive sampling for the sampling technique. The independent variables in this study are loan loss reserves, return on equity, bank size liquidity ratio and loan ratio, and capital adequacy ratio is the dependent variable. The results show that bank size and the return on equity have a positive effect on capital adequacy ratio, while loan ratio has a negative effect on capital adequacy ratio. The liquidity ratio and loan loss reserve have no effect on the capital adequacy ratio. It is expected that the results of this study will provide a reference for companies to understand the factors that affect capital adequacy. Managerial implications: Banking companies are expected to increase the total number of assets held, increase return on equity and reduce bank loan ratios to avoid the risk of bad credit.